Effects of dapagliflozin on congestion assessed by remote pulmonary artery pressure monitoring. (26th June 2020) - Mullens, Wilfried; Martens, Pieter; Forouzan, Omid; Dauw, Jeroen; Vercammen, Jan; Luwel, Evert; Ceyssens, Wendy; Kockaerts, Veerle; Ameloot, Koen; Dupont, Matthias
Abstract : Aims: To explore the effects of dapagliflozin on congestion through CardioMEMS (Abbott Inc., Atlanta, USA) and Cordella™ pulmonary artery Sensor (Endotronix Inc., Lisle, Il, USA) devices, which are implantable systems that provide real‐time remote monitoring of pulmonary artery pressure (PAP). Methods and results: Single‐centre open label observational pilot trial, to investigate the short‐term effects of dapagliflozin in consecutive heart failure and reduced ejection fraction patients with elevated PAP between October and December 2019, previously implanted with CardioMEMS or Cordella™ Sensor. Changes in PAP were evaluated with an area under the curve methodology to estimate the total sum increase or decrease in pressures (mmHg/day) for 7 days before and after starting dapagliflozin relative to the first day of each period. Nine patients (72 ± 10 years, N‐terminal pro b‐type natriuretic peptide 1027 ± 510 pg/mL, estimated glomerular filtration rate 45 ± 15 mL/kg/m2, left ventricular ejection fraction 35 ± 10%), all on optimal guideline‐directed therapy was included. The mean PAP was reduced from 42 ± 9.16 to 38 ± 9.95 mmHg with dapagliflozin therapy ( P  < 0.05). The average area under the curve for the week leading to dapagliflozin therapy remained unchanged compared to the drop observed for the week after therapy ( P  < 0.05). Interestingly, the drop in PAP occurred within the first 2 days of dapagliflozin and remained stable for the week following the start of the therapy. Conclusions: This is the first study to demonstrate a direct effect of dapagliflozin on achieving effective hemodynamic decongestion, providing further mechanistic data regarding the potential mechanisms of sodium‐glucose co‐transporter‐2 inhibitor benefits on heart failure.